Promoting the Water Oxidation Catalysis by Synergistic Interactions between Ni(OH)2 and Carbon Nanotubes. Issue 15 (31st May 2016) - Wang, Lei; Chen, Hong; Daniel, Quentin; Duan, Lele; Philippe, Bertrand; Yang, Yi; Rensmo, Håkan; Sun, Licheng
Abstract : Ni‐nanocarbon‐based hybrid materials are prepared by a two‐step simple synthetic route and investigated as an oxygen evolution reaction (OER) electrocatalyst, exhibiting low overpotential, small Tafel slope 32 mV dec –1 and a high turnover frequency ≈16 s −1 based on the Ni metal.